Demographics, self-efficacy, benefits/barriers, stages of adopting pap testing among Korean American women. (19th May 2019) - Tung, Wei-Chen; Granner, Michelle; Lu, Minggen; Sohn, Jeeyun
Abstract: Korean American women (KAW) experience the third highest incidence rate of cervical cancer among nine major Asian Americans. This study examined cervical cancer screening among KAW using constructs from the transtheoretical model (TTM). Using a cross-sectional survey design, 102 KAW aged 21–65 years of age were recruited through convenience sampling. Twenty-seven per cent of participants reported of never receiving a Pap smear. Women who were older and married were more likely to report being in the action/maintenance stages; women who perceived themselves to be in poor health were less likely to be in the action/maintenance stages. Higher self-efficacy and lower perception of barriers were significantly associated with more advanced TTM stages. The perceived benefits were not statistically different across TTM stages of change. A special attention should be given to young and unmarried KAW to increase screening participation. Impact statement: What is already known on this subject? The utilisation of Pap test among Korean American women (KAW) was low. Using the transtheoretical model (TTM) approach has the potential to increase a screening adherence. What do the results of this study add? This is the first study to examine the association between TTM constructs related to Pap testing among KAW. Younger and unmarried women reported the lowest levels of screening attitudes or behaviours; and tailored efforts may be beneficial in increasing the screening among these women. What are the implications of these findings for clinical practice and/or further research? Increasing the self-efficacy and decreasing the barriers to obtaining Pap screening are critical to move Korean women to the advanced TTM stages. Further investigation is needed with KAW to fully understand the relationships between TTM constructs.